Evaluación Tecnológica Del Equipamiento Biomédico En El Hospital Timbío - Empresa Social Del Estado (2024)
This work, carried out within the framework of an internship, focuses on the assessment of medical technology equipment at the Timbío Hospital - Empresa Social Del Estado. The methodology employed is based on the implementation of the obsolescence index guide proposed by the Ministry of Health and Social Protection. The resulting document is a comprehensive technical report, developed through the CDIO methodology. This report addresses the current state of technology comprehensively, providing a detailed analysis from various criteria, including technical, clinical, and economic aspects. The central purpose of this evaluation is to optimize decision-making related to the renewal, replacement, and acquisition of biomedical equipment. All of this with the primary goal of ensuring quality and safety in the provision of healthcare services.